Inhibition of RAS Activation Due to a Homozygous Ezrin Variant in Patients with Profound Intellectual Disability. Issue 2 (February 2015) - Riecken, Lars Björn; Tawamie, Hasan; Dornblut, Carsten; Buchert, Rebecca; Ismayel, Amina; Schulz, Alexander; Schumacher, Johannes; Sticht, Heinrich; Pohl, Katja J.; Cui, Yan; Reis, André; Morrison, Helen; et al.
<x xml:space="preserve">Abstract</x> Ras activation is inhibited by a loss‐of‐function variant of ezrin. Wild type ezrin assembles a complex containingboth SOS and Rasto drive efficient guanine nucleotide‐exchange and therebyRas activation. Active GTP‐loaded Ras subsequently drives downstream signalling cascades mediating Ras‐dependent cellular processes such as proliferation and neuronal differentiation. The ezrin variant Ala129Thr, however, is unable to bind Ras, thus precludes Ras from the complex and impedesRas activation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>